The importance of Pediatric Dentistry in identifying child sexual abuse situations (Research, Society and Development, 2021)
Introduction: Human Papilloma Virus (HPV) is a virus prevalent in the general population and is considered a sexually transmitted infection, and can be transmitted by non-sexual forms such as casual contact and vertical transmission. The virus is considered the etiologic agent of some carcinomas, inducing the appearance of pathologies such as cervical cancer and oropharyngeal cancer. When it occurs in children, it may be the first indication of sexual abuse, emphasizing that sexual assault represents the main form of contamination by human papillomavirus (HPV) in children from five years old. Objective: To report a case of diagnosis of injury from the Human Papilloma Virus (HPV) and identification of sexual abuse in a child, with the purpose of showing the importance of pediatric dentistry in the diagnosis of violence suffered by patients, raising awareness among the dental class. Results and Discussion: The closest family members are the main responsible and often the child aggressors themselves and, therefore, it is worth noting that those responsible for mistreating their children hardly take their children to the pediatric dentist more than once, in order not to be discovered4. Thus, it is up to the professional to pay attention to the child's behaviour during the consultation and carry out detailed anamnesis and clinical examination. Final considerations: In addition, the professional has the obligation of reporting cases of abuse to the competent body, thus promoting the removal of the child abuser and preventing further episodes like this from continuing to cause traumas in them.